Analisis Tindak Pidana Pencurian Dengan Kekerasan Yang Disertai Pemerkosaan Terhadap Anak SMK (Studi Putusan No 16/Pid.B/2021/Pn.Met) - Zainab Ompu Jainah; Nada Alia Husna (LPPM Universitas Dharma Andalas, 2022)
The crime of theft is a crime that is often encountered in society. There are so many types of crimes that are accompanied by theft, one of which is rape. The purpose of this study is to understand and analyze the factors that cause the perpetrators to commit the crime of theft accompanied by rape as well as the judge's considerations in imposing a crime against the perpetrator based on the decision number 16/Pid.B/2021/Pn.Met. This study uses a normative juridical method by examining the rules, norms, rules related to the problems to be studied and empirical approaches that are carried out through research exclusively on the object of research using observation and interviews. The factor causing the perpetrator to commit the crime of theft accompanied by rape is a factor that comes from within the perpetrator who commits the crime itself, without any coercion from anywhere. The judge's consideration in making a decision against the perpetrator of theft accompanied by rape was based on the decision Number 16/Pid.B/2021/Pn.Met, namely based on aggravating and mitigating circumstances for the Defendant. Aggravating circumstances include the Defendant's actions disturbing the public, the Defendant had previously been sentenced to prison for committing a crime of theft with violence in the jurisdiction of the Gunung Sugih District Court and the jurisdiction of the Metro District Court, in this case the Defendant had committed two criminal acts at the same time, namely theft with violence and rape, the Defendant in carrying out his actions are classified as sadistic, the Defendant's actions can result in the death of the victim's witness, the Defendant's actions have damaged the future of the victim's witness, the Defendant's actions have a psychological impact on the victim witness and his family. Meanwhile, there are no mitigating circumstances.